(3fGSN GdbQBf hefShNgs - (3GdHZOGOj, GHf SdGeI, CHh GdbGSe, gHI Gddg Hf SdGeI Hf fUQ Hf Ydj, (B410 (3g`s
(3BNQgG (B:s
(3aj BNQgG CfgG bhHdJ hUMMJ Ydi GdfSNI GdJj fbdJ efgG aj ChGNQ Pj GdMLI (B542(3g`s
(3eUOQ GbJfGA GdCUd (B:s
(3aGVd CMeOs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3ceGd GdfSNI (B:s
Keywords: (3GdJaSjQ hYdhe GdbQBfs